DEVELOPMENT OF AN ICE CREAM DAIRY PRODUCT USING CAÑAFISTULA PULP (Cassia fistula) AS AN ANTIOXIDANT ACTIVE INGREDIENT (Orinoquia, 2025)
The development of innovative ice creams, such as the one created with Cassia fistula within the field of food technology, opens up an exciting horizon. The unique properties of Cassia fistula can impart the product with distinctive characteristics in terms of flavor and potential health benefits; the antioxidant activity, measured by DPPH• and ABTS•+, reached values of 80,10 ± 0,30 µg/mL and 30,1 ± 0,09 µg/mL, respectively. The meticulous selection of dairy ingredients highlights not only the creation of a unique and delicious product but also the importance of striving for the highest possible quality. The results of the ice cream's sensory analysis are remarkable, showing a high percentage of acceptance (≥95%) concerning the evaluated sensory attributes, such as flavor, aroma, color, texture, and purchase intention. This innovative approach can not only meet the expectations of consumers seeking unique gastronomic experiences but also demonstrates the potential to conquer a broad market.
Keywords: Fruit, Food industry, Dairy product.